Penggunaan Alat Kontrasepsi dalam Islam dan Implementasinya terhadap Kesehatan Reproduksi - Sari, Elyse Prastika; Fawwazni, Nasywa Nayla; Alfan, Jamalul Il; Amiruddin, Muhammad (Maliki Interdisciplinary Journal, 2025)
The Islamic law on contraceptive use and its implications for reproductive health. In the modern context, contraception is a crucial issue in family planning and public health, yet its use often sparks debate among Muslims. This study outlines the views of Islamic scholars and Islamic legal arguments regarding the permissibility of contraception, emphasizing the principle of maqāṣid al-sharī‘ah, particularly in protecting offspring (ifẓ al-nasl) and maternal health. In general, Islam permits the use of temporary contraception that does not endanger health and is carried out with the consent of the husband and wife, while permanent methods such as vasectomy or tubectomy are permitted only in medical emergencies. This discussion also highlights the positive impacts of contraception, such as reducing maternal and infant mortality and improving family welfare, in addition to the risks of physiological and psychological side effects that need to be anticipated. Thus, contraception in Islam is not a rejection of God's blessings, but rather an effort to maintain family health and well-being. Collaboration between medical personnel, Islamic scholars, and the community is needed to educate about the safe, ethical, and sharia-compliant use of contraception. Contraception can provide benefits such as regulating birth spacing, protecting maternal health, and improving the quality of family life. However, its use also has negative impacts, such as menstrual irregularities, weight gain, and psychological disorders, which must be anticipated. Therefore, contraception must be understood as a legitimate form of Islamic endeavor.